2001
DOI: 10.3989/gya.2001.v52.i1.395
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of γ-irradiation and microwave treatments on the lipids and microbiological pattern of beef liver

Abstract: RESUMEN Comparación de los tratamientos por irradiación γ y microondas en los lípidos y aspectos microbiológicos del hígado de vaca.Se estudiaron los efectos de los tratamientos por irradiación γ (0, 2.5, 5 y 10 kGy) y microondas (generados en un horno a nivel bajo y de descongelación durante 0.5, 1 y 2 min) sobre la composición química y aspectos microbiológicos de las muestras de hí-gado de vaca. Los análisis químicos y microbiológicos se llevaron a cabo en hígado de vaca tratado y no tratado al inicio y dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Nowadays, the microwave oven has not only gained common and routine use for heating purposes in household, especially for defrosting, heating or cooking, but, it is used in food processing and preservation in the food industry as well (Farag, Daw, Mahmoud, & El-Wahab, 2001). Microwave heating has many advantages over conventional heating including precise timing, rapidity, and energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the microwave oven has not only gained common and routine use for heating purposes in household, especially for defrosting, heating or cooking, but, it is used in food processing and preservation in the food industry as well (Farag, Daw, Mahmoud, & El-Wahab, 2001). Microwave heating has many advantages over conventional heating including precise timing, rapidity, and energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical variations occurring in beef liver proteins due to exposure to microwaves generated at defrost oven power setting are shown in Table 5 and Fig 3. In general, the number of bands was lower in microwaved 14,15 than in non-microwaved beef liver. 16 Dramatic changes in the band type and concentration were found as a result of exposure to microwaves for different periods.…”
Section: Electrophoretic Patterns Of Non-irradiated and G-irradiated mentioning
confidence: 95%
“…14 The production of ammonia (deamination of amino acids) and the presence of fatty and keto acids as part of the radiolytic products indicated protein destruction. In addition, the total microbial counts 15 of the beef liver samples under study demonstrated the presence of associated micro-organisms. During frozen storage the microbial counts decreased and the exposure to microwaves and g-radiation caused a further reduction in microbial counts.…”
Section: Effect Of Microwave Treatments On Protein Content Of Beef Livermentioning
confidence: 99%
“…In industrial field, microwave heating has been used for many applications, including food processing and preservation, bleaching, pasteurization, and sterilization (Decareau, 1985;Farag et al, 2001;Knutson et al, 1987). Numerous advantages boosted the use of microwave heating making it in many cases a technique preferred to conventional heating.…”
Section: Introductionmentioning
confidence: 99%